High‐syn conformation of uridine and asymmetry of the hexameric molecule revealed in the high‐resolution structures of Shewanella oneidensis MR‐1 uridine phosphorylase in the free form and in complex with uridine. (1st December 2014) - Safonova, Tatyana N.; Mikhailov, Sergey N.; Veiko, Vladimir P.; Mordkovich, Nadezhda N.; Manuvera, Valentin A.; Alekseev, Cyril S.; Kovalchuk, Mikhail V.; Popov, Vladimir O.; Polyakov, Konstantin M.
<x xml:space="preserve">Abstract</x> Uridine phosphorylase (UP; EC 2.4.2.3), a key enzyme in the pyrimidine‐salvage pathway, catalyzes the reversible phosphorolysis of uridine to uracil and ribose 1‐phosphate. Expression of UP from Shewanella oneidensis MR‐1 (SoUP) was performed in Escherichia coli. The high‐resolution X‐ray structure of SoUP was solved in the free form and in complex with uridine. A crystal of SoUP in the free form was grown under microgravity and diffracted to ultrahigh resolution. Both forms of SoUP contained sulfate instead of phosphate in the active site owing to the presence of ammonium sulfate in the crystallization solution. The latter can be considered as a good mimic of phosphate. In the complex, uridine adopts a high‐syn conformation with a nearly planar ribose ring and is present only in one subunit of the hexamer. A comparison of the structures of SoUP in the free form and in complex with the natural substrate uridine showed that the subunits of the hexamer are not identical, with the active sites having either an open or a closed conformation. In the monomers with the closed conformation, the active sites in which uridine is absent contain a glycerol molecule mimicking the ribose moiety of uridine.